2015
DOI: 10.5937/ekopolj1502543c
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rural development policy on domestic violence

Abstract: Rural development policy deals with achieving goals for rural areas and a wide range of socioeconomic activities are included within it. This work intends to connect rural development policies with the occurrence of domestic violence in rural areas. The area of research is the territory of Tuzla Canton, which is, by definition of OECD (less than 150 habitants/km 2), a predominantly rural area. Domestic violence is a wide spread form of violence and a discrimination against women. Domestic violence includes all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Most of the total production value (96%) comes from the sale of honey, with subsidies accounting for only 4%. Similar to the results of several studies [6,12,[42][43][44][45], most of the total production value (96%) comes from the sale of honey, with subsidies accounting for only 4%. The model beekeeping farm produces the most acacia honey (6000 kg), which has the highest purchase price and contributes the most to production value.…”
Section: Operational Calculations: Yields Production Value Production...supporting
confidence: 85%
See 1 more Smart Citation
“…Most of the total production value (96%) comes from the sale of honey, with subsidies accounting for only 4%. Similar to the results of several studies [6,12,[42][43][44][45], most of the total production value (96%) comes from the sale of honey, with subsidies accounting for only 4%. The model beekeeping farm produces the most acacia honey (6000 kg), which has the highest purchase price and contributes the most to production value.…”
Section: Operational Calculations: Yields Production Value Production...supporting
confidence: 85%
“…In Romania, Popescu [50] found that beekeepers must keep more than 100 bee colonies to be profitable. In Bosnia and Herzegovina, the model described by Cejvanovic et al [42] puts the economic farm size at 200-350 bee colonies.…”
Section: Fc (Fixed Costs Eur)mentioning
confidence: 99%